Pembangunan Aplikasi Social Geotagging Destinasi Wisata Berbasis Android - Ulfani Defitria; Bayu Priyambadha; Denny Sagita Rusdianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Traveling has become a lifestyle for someone to fill their spare time or hobby. Tourism activity can not be separated from the documentation as a means to commemorate the tourist event. Nowadays, the development of mobile technology has been equipped with a digital camera in it, so it can be used easily to take photos of tours for the visitors. With the support of Internet network, it is possible for tourists to distribute photos in order to be enjoyed by many people in a short time through intermediaries of social media. Mobile devices such as smartphones currently supports cameras that have geotagging feature, so that the location of shooting can easily to known. There are some various references are scattered in various print and electronic media. These media are less effective in providing information, it is because of the searching of information from unregulated sources, so it takes a long time to look for them. So that the information can be obtained easily, with a reference tours are collected in a container in the form of community is easily to accessed by recommendations provide based on supporting factors such as distance, time, and cost. This research begins by analyzing system requirements, then performing design and implementation phases. In this study apply the geotagging feature to get the location of the tourist photos and haversine formula to search the nearest location. The testing is done by using unit testing, validation testing, and compatibility testing. The results of the validation testing indicate that the built system has been run in accordance with its function in both of normal function and alternative conditions, and compatibility test results indicate that the built system runs well on different versions of Android operating system.